Liver Dysfunction Associated with Intravenous Methylprednisolone Pulse Therapy in Patients with Graves’ Orbitopathy - Hiroyuki Eguchi; Junichi Tani; Saori Hirao; Munehisa Tsuruta; Ichiro Tokubuchi; Kentaro Yamada; Masataka Kasaoka; Yasuo Teshima; Tatsuyuki Kakuma; Yuji Hiromatsu (International Journal of Endocrinology)
Intravenous methylprednisolone (IVMP) pulse therapy is the first-line treatment for the active phase of moderate to severe Graves’ orbitopathy (GO). However, acute and severe liver damage has been reported during and after IVMP therapy. In this retrospective study, we investigated risk factors for liver dysfunction during and after IVMP therapy based on 175 Japanese patients with moderate to severe GO and treated at our center between 2003 and 2011. The results showed that seven patients developed severe liver dysfunction with elevated serum alanine aminotransferase (ALT > 300 U/L). Mild (40–100 U/L) and moderate (100–300 U/L) increases of ALT occurred in 62 patients (35%) and 10 patients (6%), respectively. Liver dysfunction was more frequently observed in males, in patients receiving high-dose methylprednisolone, and patients aged over 50 years. Preexistent viral hepatitis was significantly associated with liver dysfunction (65% in patients positive for hepatitis B core antibody and patients positive for hepatitis C virus antibodies). Our study confirmed the association of liver dysfunction with IVMP during and after treatment. It suggests that, in patients with GO, evaluation of preexisting risk factors—including viral hepatitis—and careful weekly monitoring of liver function during IVMP therapy and monthly thereafter for 12 months are warranted.